1969
DOI: 10.1104/pp.44.8.1108
|View full text |Cite
|
Sign up to set email alerts
|

Iron Accumulation, Root Peroxidase Activity, and Varietal Interactions in Soybean Genotypes That Differ in Iron Nutrition

Abstract: Abstract. Four soybean g-notypes (Glycine mnax L. Merrill) differing in their ability to accumu!ate iron were studied: the efficient genotypes Hawkeye (HA) and A62-9 (E-9) and the inefficient g-notypes PI-54619-5-1 (PI) ar.d A62-10 (1-10).The distr.bution of iron in the tissues of plants grown in a growth chamber in nutrient solutions containing various levels of iron was determined. A greater amount of iron was associat-d with the roots of inefficient plants than with roots of efficient plants, indicating a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

1970
1970
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 23 publications
3
6
0
Order By: Relevance
“…They found that the soybean variety that was inefficient in accumulating Fe caused a reduction in Fe uptake by the variety that was efficient. These results were confirmed by Elmstrom and Howard (1969) from plants grown in a growth chamber in nutrient solutions containing various levels of Fe.…”
Section: Discussionsupporting
confidence: 62%
“…They found that the soybean variety that was inefficient in accumulating Fe caused a reduction in Fe uptake by the variety that was efficient. These results were confirmed by Elmstrom and Howard (1969) from plants grown in a growth chamber in nutrient solutions containing various levels of Fe.…”
Section: Discussionsupporting
confidence: 62%
“…This observation has never been reported before. It has been shown that efficient soybean plants generally are the shortest (Elmstrom and Howard 1969), suggesting a negative correlation between stem length and IDC tolerance. Perhaps the large amounts of Fe being channelled to bigger unifoliolate leaves impair the Fe that is left for remobilization to the trifoliates, which are emerging after the unifoliolates.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of iron is one of the more common nutrients associated with chlorosis. However, zinc deficiencies in the soybean plant will also cause chlorosis (Elmstrom and Howard 1969;Sliman and Motto 1990). When looking at Zn cotyledon concentration and remobilization, no significant correlation was found to SPAD values.…”
Section: Discussionmentioning
confidence: 99%
“…Freshly prepared nutrient solution used for culturing plants had the following composition in millimoles per liter: Ca(N03)2.4H20, 0.63; Mg(NO3)2.6H20, 0.14; K21HPO4, 0.22; NH4NO3, 0.11; KNO3, 0.03; (NH4)ZS04, 0.07, and in ymoles per liter: MnCl2.4H20, 1.18; ZnSO4.7H20, 0.31; CuS04-5H20, 0.08; H3B03, 3.29; Na2MoO4.2H20, 0.05. In all instances the pH of the nutrient solution decreased from initial values of about 7.5 to about 4.2 during the 7-day absorption period (6).…”
Section: Materalis and Methodsmentioning
confidence: 99%
“…Two efficient soybean genotypes-Hawkeye (HA) and E62-9 (E-9)-and two inefficient genotypes-PI-54619-5-1 (PI) and A62-10 (1-10)-were grown in a growth chamber as described previously (6). Seeds of the four genotypes were allowed to germinate in a plastic tray of distilled water.…”
Section: Materalis and Methodsmentioning
confidence: 99%